PERLINDUNGAN HUKUM TERHADAP PELAPOR TINDAK PIDANA (WHISTLEBLOWER) DALAM TINDAK PIDANA NARKOTIKA - Milzam, Fathan Taris; Sutrisno, Sutrisno (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Whistleblowers who expose illegal activities, generally, have their own fears, which hinder the process of reporting drug crimes. This necessitates the need for legal protection provided by the state as an effort to safeguard and uphold the law. This research aims to understand and analyze how individuals reporting drug crimes can be categorized as whistleblowers entitled to legal protection under the existing laws in Indonesia, as well as to identify and analyze the forms of legal protection available to whistleblowers of drug crimes based on the applicable legal regulations in Indonesia. The research methodology used in this research is normative juridical with statute approach and conceptual approach. The data analysis method used is qualitative normative analysis of primary and secondary data. The results of this study indicate that legal protection for whistleblowers refers to the Republic of Indonesia Law No. 31 of 2014 about the Amendment to Law No. 13 of 2006 about Witness and Victim Protection. In this context, legal protection is provided by the LPSK (Witness and Victim Protection Agency), which is authorized to protect whistleblowers. The forms of legal protection include physical and psychological protection for whistleblowers, as well as special handling and legal protection measures for whistleblowers